Education facilitating students' comfort with LGBT people - Craig, Samantha; Wydra, Tess. (My University, 2009)
Intolerance for the lesbian, gay, bisexual and transgender (LGBT) community is often intensified by a lack of knowledge and understanding between heterosexuals and the LGBT community(Getz & Kirkley, 2006). The central question in this study was ?What is the relationship between education on the college campus and one's comfort level with LGBT people?? The researchers predicted that those students who have received education on LGBT issues would be more comfortable with the LGBT population than those students who did not. Participants were N = 55 students from a university in Wisconsin in this nonrandom pilot study. Survey data was statistically analyzed using frequencies, crosstabulations, mean comparisons, and a reliability analysis. Results indicated and supported the hypothesis that receiving education on a college campus can make an individual more comfortable with the LGBT population. Specific implications for practitioners would be to include LGBT topics and/or issues into their curriculum to provide more information to students in order to increase their comfort levels of the LGBT population.
Keywords: Homosexuality and education; Sexual orientation--Study and teaching; College students--Attitudes